Clenched Subjectivity: Disability, Women and Medical Discourse - Tanya Titchkosky (Disability Studies Quarterly, 2005)
Situated at the intersection of disability and feminist theory, this paper conducts an analysis of a way that women and disability are made meaningful in everyday life. The paper analyzes a seemingly ordinary newspaper story of disability; the story begins by telling of a woman who knowingly remains pregnant with a disabled fetus; goes on to provide statistics of similar cases and ends narrating the lives of families with disabled members. Bypassing the pro-choice/pro-life form of argument, I delve into the newspaper's medicalized textual rendering of disability and women and show how the meanings of both are enacted. I demonstrate the ways that text organizes the reader's consciousness so as to reproduce women as the embodiment of uncontrollable subjectivity and reproduce disability as nothing other than devalued lack. By interrogating the processes involved in medicalizing life through its technologies, the paper exemplifies the socio-political necessity of regarding text as a form of social action in need of critical analysis.
Keywords: sociology of knowledge; medical discourse; Disability Studies; women; fetal abnormality; meaning making; textual enactment.